Pre-Eruptive Magma Configurations and Petrogenetic Relationships of the Rattlesnake Tuff, Oregon–Insights From Spectacularly Banded High-Silica Rhyolite Pumices - Swenton, Vanessa M.; Streck, Martin J. (Frontiers in Earth Science, 2022)
The 7.05 Ma Rattlesnake Tuff (RST) of eastern Oregon is a widespread (>300 km3), variably welded ignimbrite sheet composed of 99% high-silica rhyolite (HSR), <1% dacites, and <<0.1% mafic inclusions that are found within the dacites. The RST HSR is comprised of five increasingly evolved compositional Groups (E, D, C, B, and A) distinguished by trace element variations. HSRs range from white to dark grey, where variations in FeO* dictate color. Previous workers interpret Groups as rhyolites generated by crystal fractionation occurring at the magma chamber roof and walls, where a series of more evolved rhyolite melts formed from relatively less evolved rhyolite parents within the chamber, resulting in a density and compositionally zoned magma chamber and compositional clustering. Mafic inclusions indicate underpinning of primitive high-Al olivine tholeiite magma was the driving mechanism that produced the enriched basaltic andesite ponded beneath the rhyolite reservoir. Dacite pumices result from disturbing the density boundary between the rhyolites and basaltic andesites during eruption of the RST. We collected 15 banded HSR pumices and isolated material from individual bands for geochemical analysis. Statistical analysis of old and new data verified these five compositional Groups and gaps characterized by variations in Ba, Eu/Eu*, Eu, FeO*, Hf, and Zr. Wet-liquidus temperatures, storage temperatures, and storage pressures calculated for all HSR Groups indicate similar pre-eruptive conditions (~6.1–7.5 km depth; storage temperatures of ~805–895oC). Fractionation trends, trends in storage pressure and temperature, and lack of crystal-rich inclusions or country rock corroborate existing models for RST HSRs that involve a single, density-stratified magma chamber. Increasing water content 2–4 wt.% from Groups E-A creates a density difference sufficient to prevent convection between layers of HSRs in a single chamber. Alternatively, if HSRs do not represent a liquid line, it is possible to generate RST HSRs through batch melting of various regional country rock. Similarly, HSRs would accumulate within the same storage zone, where density variations kept HSRs from mixing until eruption. In either scenario, our study underscores the significance of water content and density variations in RST HSR magma storage and configuration and in generating these strikingly banded HSR pumices.